A solid-state NMR investigation of structure and dynamics in nucleosides and methylated DNA oligonucleotides - Geahigan, Karen Brigitte (My University, 1998)
This dissertation contains various experimental solid-state NMR techniques for probing structure and dynamics in nucleosides and DNA oligonucleotides. One- and two-dimensional solid-state NMR experiments were applied to four different nuclei in these investigations: $\sp$C, $\sp$N, $\sp$F, and $\sp2$H. One-dimensional homonuclear dipolar recoupling experiments (i.e. Radio Frequency Driven Dipolar Recoupling (RFDR) and Dipolar Recoupling with a Windowless Sequence (DRAWS)) were used to measure internuclear $\sp$C-$\sp$C and $\sp$F-$\sp$F distances in (2,1$\sp\prime$-$\rm\spC\sb2\rbrack$- and (2,2$\sp\prime$-$\rm\spC\sb2\rbrack$-cytidine and the DNA dodecamer sequence, (d(CGCGAATT$\rm\sp{5Me}$CGCG)) $\sb2,$ which contained either (2-$\sp$C) -thymidine or (5-$\sp$F) -2$\sp\prime$-deoxyuridine at the T$\sb8$ and (2-$\sp$C) -5-methyl- or (5-$\sp$F) -2$\sp\prime$-deoxycytidine at the C$\sb9$ positions. These measurements indicate that methylation produces minimal distortion of the local geometry at the T$\sb8$-C$\sb9$ dinucleotide junction. Two-dimensional DRAWS and RFDR experiments were used for the chemical shift assignment of complicated multiply $\sp$C, $\sp$N labeled nucleosides. Double-quantum (DQ) DRAWS was also applied to various selectively and uniformly $\sp$C enriched nucleoside monomers in order to obtain orientational information for pairs of dipolar coupled nuclei. Our findings demonstrate that solid-state dipolar recoupling methods can provide valuable structural information about nucleosides and nucleic acids in polycrystalline and heterogeneous environments.Solid-state deuterium NMR experiments were also implemented to probe the internal motions of the sugar ring, backbone, and base moieties of 5-methyl-2$\sp\prime$-deoxycytidine incorporated at the C$\sb9$ position in the DNA dodecamer, (d(CGCGAATT$\rm\sp{5Me}$CGCG)) $\sb2,$ as a function of hydration level. Replacement of the C$\sb9$ residue with its methylated analogue radically perturbs the large-amplitude dynamics of the exocyclic methylene group but only marginally alters the mobility of the furanose ring that was noted in a previous study by Hatcher and coworkers (70). Base mobility in methylated and unmethylated derivatives was found to be similar. Reduced flexibility of the $\rm\sp{5Me}C\sb9$ site may be directly correlated with inhibition of hydrolysis by the EcoRI restriction enzyme. The solid-state $\sp2$H NMR findings indicate that there may be a dynamic component in the sequence-specific protein-DNA recognition mechanism that is hindered by methylation of the C$\sb9$ residue.
Thesis (Ph. D.)--University of Washington, 1998
Keywords: Theses--Chemistry